Criminal procedure and the Supreme Court : a guide to the major decisions on search and seizure, privacy, and individual rights - Del Carmen, Rolando V.; Hemmens, Craig (Craig Thomas), 1960-; Bell, Valerie (Valerie R.) (Lanham, Md. : Rowman & Littlefield Publishers, 2010)
Placed in context with an introductory and concluding chapter, this book provides a summary and analysis of the 20 most significant Supreme Court cases dealing with criminal procedure, which have had the greatest impact on police investigatory practices and prosecutorial conduct. These cases have defined the parameters of police and prosecutorial activities and are crucial to an understanding of the law of search and seizure and criminal prosecution.
Reasonable expectation of privacy and probable cause -- The exclusionary rule -- Stop and frisk -- Arrest -- Searches of places and things -- Motor vehicles -- Interrogation and lineups -- Police liability -- The next twenty most significant cases -- Timeline of significant Supreme Court cases dealing with police investigatory practices -- Biographies of select United States Supreme Court justices.
Includes bibliographical references (p. 349-355) and index.
Keywords: Searches and seizures -- United States -- Cases; Civil rights -- United States -- Cases; Privacy, Right of -- United States -- Cases; Criminal procedure -- United States -- Cases; Criminal investigation -- United States -- Cases; United States. -- Supreme Court; Judges -- United States -- Biography; United States. -- Supreme Court; Civil rights; Criminal investigation; Criminal procedure; Privacy, Right of; Searches and seizures; United States; Trials, litigation, etc